2021
DOI: 10.9758/cpn.2021.19.3.449
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Alterations Associated with Pro-inflammatory Cytokines in Patients with Major Depressive Disorder

Abstract: Objective: Regarding the neuroinflammatory theory of major depressive disorder (MDD), little is known about the effect of pro-inflammatory cytokines on white matter (WM) changes in MDD. We aimed to investigate the relationship between pro-inflammatory cytokines and WM alterations in patients with MDD. Methods: Twenty-two patients with MDD and 22 healthy controls (HC) were evaluated for brain imaging and pro-inflammatory cytokines including interleukin (IL)-1, IL-6, IL-8, interferon- and tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 71 publications
2
20
3
Order By: Relevance
“…Another study compared 22 patients with MDD and 22 healthy subjects. They reported similar findings, showing that peripheral concentrations of TNF were negatively correlated with FA in several white matter regions, including the corpus callosum and both the left anterior and superior corona radiata [28]. In one study that pooled MDD and healthy control participants (n = 590), the results indicate that methylation-based measures of CRP were associated with widespread reductions in FA, and the strongest relationships were found in the external capsule and the anterior limb of the internal capsule [29].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Another study compared 22 patients with MDD and 22 healthy subjects. They reported similar findings, showing that peripheral concentrations of TNF were negatively correlated with FA in several white matter regions, including the corpus callosum and both the left anterior and superior corona radiata [28]. In one study that pooled MDD and healthy control participants (n = 590), the results indicate that methylation-based measures of CRP were associated with widespread reductions in FA, and the strongest relationships were found in the external capsule and the anterior limb of the internal capsule [29].…”
Section: Introductionsupporting
confidence: 54%
“…These findings bear some similarity to results attained by other studies, but also shed new light on the relationship between systemic inflammation and white matter integrity in depression. Previous studies have reported inverse associations between proinflammatory cytokines in the periphery (i.e., IL-1β and TNF) and corpus callosum integrity (indexed by FA value) [27,28]. The corpus callosum is the most prominent forebrain commissure connecting the left and right hemispheres, and is only found in placental mammals [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Another probable reason might be group-related differences between depression participants. There is only one study with the voxelwise approach that showed a connection between TNF-a and FA in depression [33], which, however, differs from the results of the current study and the study cited above [29]. To speculate, individual differences could account for the different outcomes, i.e., macrophages, for example, produce cytokines, IL-1b and TNF-a, which have an inflammatory effect [61].…”
Section: (Running Title: Fractional Anisotropy and Inflammation In De...contrasting
confidence: 78%
“…In a volumetric MRI study by Frodl et al, participants with depression who were not drug-naïve showed smaller hippocampal volumes but higher IL-6 concentrations [34]. Two further DTI studies showed negative correlations between the FA values of various WM fiber tracts and peripheral inflammatory cytokines (i.e., and TNF-⍺) in patients with a first episode or drug-naïve depressed patients [29,33].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation